Artificial Inteligence (Ai) Terhadap Dunia Pendidikan - Harefa, Efrat Ferson; Harefa, Everlasting Grace (CV. SINAR HOWUHOWU, 2025)
The application of Artificial Intelligence (AI) in the field of education has created new opportunities to improve the quality of learning and expand access to education. This study aims to analyze the benefits, opportunities, and challenges offered by AI in the educational context. Using a qualitative descriptive approach, data were collected through literature reviews, interviews with educators and technology experts, and analysis of AI-based learning platforms. The results of the study show that AI plays a significant role in supporting personalized learning, reducing teachers' administrative burdens, and enhancing educational inclusion. However, challenges such as technological disparities, data privacy, and a lack of teacher training remain major obstacles. With adequate infrastructure, data protection regulations, and training for educators, AI has the potential to become a revolutionary tool in creating a more adaptive and inclusive education system.